Diversity, Distribution Pattern, Morphometric of Box Mussel Septifer bilocularis (Linnaeus, 1758) on the Reef Flat in Cape Lampangi, South Minahasa - Grace Mustamu; Lawrence J. L Lumingas; Anneke V. Lohoo (Sam Ratulangi University, 2014)
Septifer bilocularis (Linnaeus, 1758) is a suspension feeder organisms which are found live clustered on dead coral . This study aims to estimate the average density, analyzes the distribution patterns and analyze morphometric aspects of a long-high (thick) relation, length-total weight relation and length-weight index without shell relation of S. bilocularis at that location. Sampling method using transect squares method, with the length of each line is 50m, on each transect placed 10 squares (measuring 1m x 1m). Based on the data analysis of the average density in both transect was 214 individuals with a clustered deployment pattern, with a maximum shell length of 29,64mm. The relation between length and high of shell shows that the growth is allometri negative, length and total weight shell relationships is allometri negative, where the contents of the weight index does not increase with increasing length but declined. Box mussel Septifier bilocularis live clustered with very dense aggregations in intertidal reef flat area on the intertidal zone are exposed at the lowest tide at Cape Lampangi. Keywords : box mussel, morphometric, Cape Lampangi, South Minahasa ABSTRAK Septifer bilocularis (Linnaeus, 1758) merupakan organisme pemakan suspensi yang banyak ditemukan hidup secara mengelompok pada rataan terumbu karang mati. Penelitian ini bertujuan untuk menduga kepadatan rata-rata, menganalisis indeks dispersi atau pola sebaran dan menganalisis aspek morfometrik berupa hubungan panjang-tinggi (tebal), panjang-berat dan panjang-indeks berat tubuh tanpa cangkang dari S. bilocularis di lokasi tersebut. Pengambilan sampel menggunakan metode transek kuadrat, dengan panjang setiap garis 50 meter, pada masing-masing transek diletakkan 10 kuadrat (berukuran 1m x 1m). Berdasarkan analisis data kepadatan rata-rata secara keseluruhan (kedua transek) adalah 214 individu dengan pola penyebaran mengelompok, dengan panjang cangkang maksimum 29,64mm. Hubungan pertumbuhan panjang dan tinggi cangkang ‘allometri negatif’, hubungan panjang cangkang dan berat total ‘allometri negatif’, di mana pertambahan indeks isi tidak sejalan dengan pertambahan panjang tetapi menurun. Kerang kotak Septifier bilocularis hidup mengelompok dengan agregasi yang sangat padat di daerah intertidal rataan terumbu pada zona intertidal yang terekspos pada saat surut terendah di Tanjung Lampangi. Kata kunci : karang kotak, morfometrik, Tanjung Lampangi, Minahasa Selatan